PENGARUH PENGUNGKAPAN TATA KELOLA PERUSAHAAN, RETURN ON ASSET, LEVERAGE TERHADAP TAX AVOIDANCE YANG TERDAFTAR DI BEI - Felix Jonathan, Estralita Trisnawati (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study is to obtain empirical evidence on the effect of corporate governance, return on asset, leverage to tax avoidance that listed in Indonesia Stok Exchange, with a total of 46 samples. This study uses secondary data which were tested using software SmartPLS 3,0. The result of this study suggests that corporate governance and leverage does not significantly influence tax avoidance. However, return on asset have positive and significant influence tax avoidance.